BENEFIT OF USING APPLIED BEHAVIOR ANALYSIS (ABA) IN STIMULUSING SPEECH IN AUTISTIC CHILDREN - Souza de Sá, Priscilla (Revista Gênero e Interdisciplinaridade, 2024)
This Course Conclusion Paper’s main focus is to address the benefit of using Applied Behavior Analysis (ABA) in stimulating speech in children with Autism Spectrum Disorder (ASD). ABA is a methodology based on behavioral principles that aims to improve and strengthen socially important behaviors, including communication skills. The main objective of this research is to indicate the benefits of using Applied Behavior Analysis (ABA) to stimulate speech in autistic children. The aim is to analyze how this methodology can contribute to the development of these children’s communicative skills, promoting their better social inclusion and quality of life. The research question that guides this study is: “What are the benefits of using Applied Behavior Analysis (ABA) in stimulating autistic children? And why does this method have better results?” To answer this question, a literature review, case study analysis and direct observation in therapeutic contexts were carried out. The results indicate that ABA, when applied correctly and consistently, can generate significant progress in the development of speech and the general communicative capacity of children with autism. This should be an individualized structure and the focus on positive reinforcement that characterizes this approach. This work hopes to contribute to the understanding of the benefits of ABA in the field of Speech Therapy and to the promotion of more effective therapeutic practices in the treatment of children with ASD.